Geometric Super-resolution using Negative Rect Mask - Haq, Ihtsham ul; Mudassar, Asloob A. (Optik (Stuttgart), 2018)
In an electronic imaging system, image is retrieved using a Charged Coupled Device (CCD). Its finite pixel size integrates the optical information and limits the spatial resolution, whereas pixel-pitch provides the sampling interval. Spatial resolution can be improved if pixels of smaller sizes are used or equivalently if Geometric Super-Resolution technique is achieved. In this paper, we are reporting use of the Negative rect mask (NRM) at image plane to achieve Geometric Super-resolution through sub-pixeling. The NRM is scanned over CCD in sub-pixel steps and image data is gathered. The target is assumed to be static during the scanning process. The data collected through CCD with NRM coding and the position information of the scanning mask provides a mean to render the geometrically super resolved image. The work is demonstrated in one and two dimensions with computer simulation. The results are also applicable on CMOS based imaging.